2018
DOI: 10.1080/09581596.2018.1550253
|View full text |Cite
|
Sign up to set email alerts
|

Pesky metrics: the challenges of measuring ART adherence among HIV-positive adolescents in South Africa

Abstract: The global rollout of antiretroviral treatment (ART) for HIV is one of the largest public health interventions ever undertaken. As the rollout expands, a growing body of research has focused on adherence to ART: how is it measured, what are the flaws of these metrics, and how may these be improved? We provide an overview of current, critical developments in adherence research among adolescents, and of how research on adherence to ART among adolescents within hyper-epidemic contexts has challenged definitions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…At two study waves (0 and 18 months follow-up), adolescents completed tablet-based surveys in their preferred language, with the support of research assistants trained in working with South African adolescents. Surveys assessed adolescents’ experiences at home, in their communities, and in healthcare settings, and questions were developed to be understandable and non-stigmatising through extensive stakeholder consultation, including with South African adolescents living with HIV [ 16 , 17 ]. For the present analyses, self-reported data were only used to determine participants’ sociodemographic and treatment-related characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…At two study waves (0 and 18 months follow-up), adolescents completed tablet-based surveys in their preferred language, with the support of research assistants trained in working with South African adolescents. Surveys assessed adolescents’ experiences at home, in their communities, and in healthcare settings, and questions were developed to be understandable and non-stigmatising through extensive stakeholder consultation, including with South African adolescents living with HIV [ 16 , 17 ]. For the present analyses, self-reported data were only used to determine participants’ sociodemographic and treatment-related characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Self‐reported measures of adherence remain common in both social surveys and clinical settings and may assist to identify adolescents at risk of virologic failure and poor health [ 15 ]. Given the scale of the epidemic in the region, particularly among adolescents and young people in South Africa, it is crucial to understand the rates of sustained ART using longitudinal designs and rigorous measures of adherence [ 16 , 22 ]. Therefore, this study utilized the self‐reported measures of adherence to describe rates of sustained ART adherence in ALHIV and assess consistency in adherence over the three waves of data collection within a large cohort of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The surveys were developed to be nonstigmatizing and easily understandable through extensive consultation with stakeholders. 28,29 Surveys were available in both English and Xhosa. These surveys are available at www.mzantsiwakho.co.za.…”
Section: Methodsmentioning
confidence: 99%